Structural Change and Energy Productivity in Türkiye - Sak, Ali Kursat; Guloglu, Bulent (International Journal of Energy Economics and Policy, 2025)
This paper examines the relationship between structural change and aggregate energy productivity in Türkiye from 1978 to 2019. Using a three-sector model the research quantifies sectoral labor and energy productivities relative to the United States, serving as a benchmark. The findings reveal that while Türkiye initially exhibited higher energy productivity than the U.S. across all sectors, this advantage diminished significantly over the study period. Only the manufacturing sector experienced positive energy productivity growth in Türkiye. Declines in agriculture and services were substantial, emerging as key drivers of the aggregate energy productivity gap between the two countries. A decomposition analysis highlights the dominant role of within-sector energy productivity changes, particularly the negative contribution of services in Türkiye, in explaining the overall decline in aggregate energy productivity. The study underscores the need for sector-specific policies targeting energy productivity improvements, particularly in services, to meet its target of a 35% absolute reduction in emission by 2030. The findings contribute to the literature by providing, for the first time, estimates of relative sectoral energy productivities for Türkiye, offering valuable insights for policymakers focused on enhancing national energy productivity.